Efforts to increase public knowledge regarding the prevention of covid-19 in Baubau City - Sadat, Anwar; Wijaya, Andy Arya Maulana; Lawelai, Herman; Asrin, Asrin; Nurlinda, Nurlinda; Saputri, Meri Meliyanti; Nursalin, Nursalin; Yanto, La (Community Empowerment, 2021)
The Corona Virus (Covid-19) is causing panic everywhere. Hundreds of thousands people were infected and thousands more died. The Indonesian government itself has given appeals to the community in overcoming this epidemic, so that it runs effectively and efficiently. However, in reality there are still many Indonesian people who do not heed this appeal. Therefore, this community service activity aims to assist the government in increasing public knowledge about preventing Covid-19. The method used in community service is carried out through counseling and mentoring. This activity is able to increase public knowledge and understanding about the dangers of Covid-19 and efforts to protect themselves from the implementation of 3M.